Esophageal Leiomyomatosis – An Unusual Cause of Pseudoachalasia - Sukanta Ray; Sundeep Singh Saluja; Ruchika Gupta; Tushar Kanti Chattopadhyay (Canadian Journal of Gastroenterology)
Esophageal leiomyomatosis is a rare hamartomatous disorder with varied presentation. In the literature, it is described mostly in children, and is associated with Alport’s syndrome. A case of leiomyomatosis that presented as achalasia not associated with Alport’s syndrome is described in a 35-year-old woman with a 16-year history of dysphagia. Barium swallow showed a smooth narrowing at the lower end of the esophagus with a longer than usual stricture length. Endoscopy showed a dilated esophagus with a submucosal nodule in the region of the cardia. A computed tomography scan revealed circumferential thickening of the esophagus involving the gastroesophageal junction, with fat planes maintained with the adjacent structure. Endoscopic ultrasound demonstrated a lesion arising from the muscularis propria. The manometry findings were suggestive of achalasia. She underwent transhiatal esophagectomy with gastric pull-up.